Retreatment of failed revascularization/revitalization of immature permanent tooth – A case report - Žižka, Radovan (J Clin Exp Dent, 2018)
The aim of this article is to describe the clinical case of the non-surgical retreatment of a failed revascularization/revitalization treatment (RRT). The retreatment was preceded by two sessions including an interim medication with calcium hydroxide and a modified irrigation protocol containing a highly-concentrated sodium hypochlorite and prolonged usage of ethylenediaminetetraacetic acid (EDTA) to reverse unacceptable side effects of hypochlorite. During a 15- month follow-up, the healing of the periapical lesion, increased thickening of root canal walls and maturation of root was apparent. The repeated RRT represents a possible treatment modality for s failed RRT. Key words:Retreatment, revascularization, revitalization, maturogenesis, immature tooth.